Combined Fixed‐Bed Reactor and In Situ DRIFTS Tests of NO Adsorption on a NOx Storage‐Reduction System Catalyst. Issue 2 (11th November 2013) - Wu, Dong L.; Tschamber, Valerie; Limousy, Lionel; Michelin, Laure; Westermann, Alexandre; Azambre, Bruno; Fechete, Ioana; Garin, François
Abstract The effect of water on NOx storage performance of a Pt/BaO/Al2O3 catalyst was investigated. The adsorption capacity of a model NOx storage‐reduction system (NSR) catalyst was studied in the presence of NO, oxygen, and water in nitrogen. Fixed‐bed and in situ DRIFTS adsorption tests were carried out in order to evaluate the influence of water on the adsorption capacity of the catalyst, adsorbed species on the surface of the catalyst, and stability of these species. The presence of water slightly reduces the NOx storage capacity of the NSR catalyst. A decrease of platinum oxidation activity was observed which was correlated to a slowdown of surface bidentate nitrate formation, detected by in situ DRIFTS tests. On the other hand, surface monodentate nitrates were favored and formation of bulk nitrates was not affected. A set of reactions corresponding to these observations is proposed.